Species richness and diversity of a fish community in a temporal water body at Caño Negro National Wildlife Refuge, Costa Rica - Sáenz Sánchez, Idania; Protti Quesada, Maurizio; Cabrera Peña, Jorge (Revista de Biología Tropical, 2006)
We evaluated fish community, species richness and diversity in a temporal water body of Río Frío, Caño Negro National Wildlife Refuge. These evaluations were done for three categories of water levels: low (below 1.5 m), intermediate (between 1.5 and 3.0 m) and high (deeper than 3 m). A total of 10 264 individuals were collected (nine families, 18 genera and 21 species). The most abundant species were Poecilia gillii (37%) and Astyanax aeneus (19%) and the least abundant were Ophisternon aenigmaticum (0.06%) and Rhamdia nicaraguensis (0.05%). The highest values in diversity (H’= 2.07), in the inverse of the Simpson index (1/D=6.2) and of the Berger-Parker (1/d= 4.2), were recorded in the deepest water category. Diversity differed clearly among water levels (p<0.001). The high and intermediate categories were the most similar (conglomerate analysis: 72.9%). Out of the 21 species captured, only O. aenigmaticum constitutes a new record for the ichthyofauna of Río Frío in the Caño Negro National Wildlife Refuge. The temporal water body of the Río Frío, considered in this study in the Playuela sector of Caño Negro National Wildlife Refuge is a non- homogeneous ichthyological system.